Brain-to-brain synchrony during dyadic action co-representation under acute stress: evidence from fNIRS-based hyperscanning - Lin, Suqin; Zhao, Hanxuan; Duan, Haijun (Frontiers in Psychology, 2023)
Unexpected acute stressors may affect our co-representation with other co-actors when completing the joint tasks. The present study adopted the emergent functional near-infrared spectroscopy (fNIRS)-based hyperscanning method to explore the brain-to-brain synchrony when implementing the Joint Simon Task under acute stress induced in the laboratory. The behavioral results reported that the joint Simon effect (JSE) was found in both the stress group and the control group, but the joint Simon effect in the stress group was significantly lessened than the joint Simon effect in the control group, demonstrating that when completing the joint action task in the state of acute stress, women’s ability to distinguishing self- from other-related mental representations was improved, and the strength of women’s action co-representation was diminished. The fNIRS results showed that when completing the joint Simon task in the state of the acute stress, the brain-to-brain synchrony at the r-TPJ in the stress group was significantly higher than that in the control group, demonstrating that the increased brain-to-brain synchrony at the TPJ may be served as the critical brain-to-brain neural mechanism underlying the joint action task under acute stress.